PLA Double‐Spirals Offering Enhanced Spatial Extensibility - Mohsen Jafarpour; Stanislav N. Gorb (Macromolecular Materials and Engineering)
Abstract Inspired by natural spiral curves, this study aims to present a strategy to find a compromise between extensibility and load‐bearing capacity in structures made from polylactic acid (PLA) as a brittle material. Herein, four geometrically distinct double‐spiral modules are fabricated using a three‐dimensional (3D) printer and subjected to tension, in‐plane sliding, and out‐of‐plane sliding to assess both their in‐plane and out‐of‐plane mechanical performance. Subsequently, a modular spiral‐based metastructure is developed and tested under tension in two different directions. The results show that the maximum extension of the modules under different loading scenarios varies from 9 to 86 mm, while their load‐bearing capacity ranges between 18 and 78 N. These significant variations highlight the considerable influence of both geometry and loading conditions on the mechanical behavior of the double‐spiral modules. Moreover, the 250% horizontal and 130% vertical extensibility of the metastructure emphasize the importance of the spatial orientation of the modules in determining the efficiency of spiral‐based metastructures. This study suggests that double‐spirals with adjustable mechanical properties, if designed rationally, can offer a promising strategy to address the limited deformability of materials like PLA, and when arranged in specific spatial configurations, they can contribute to the development of energy‐dissipative metastructures with enhanced extensibility.